KMT2C mutation as a predictor of immunotherapeutic efficacy in colorectal cancer - Chunhua Ni; Xiaohong Wang; Shaoping Liu; Junling Zhang; Zhongguang Luo; Bei Xu (Scientific Reports, 2024)
Abstract Immunotherapy had shown good antitumor activity in a variety of solid tumors, but low benefit in CRC, so there was an urgent need to explore new biomarkers. We evaluated the role of KMT2C using publicly available data from the Cancer Genome Atlas (TCGA) and Memorial Sloan Kettering Cancer Center (MSKCC). In addition, further analysis was performed in an internal cohort. Moreover, the mutant profiles of KMT2C was analyzed in a large CRC cohort. The relationship between clinical pathologic features and KMT2C were analyzed with using the two-sided chi-squared test or the Fisher exact test. Clinicopathologic characteristics associated with overall survival using Cox regression and the Kaplan–Meier method. We found that KMT2C-mutated CRC patients in the immunotherapy cohort had significantly improved OS compared with KMT2C WT patients (P = 0.013). However, this phenomenon did not exist in non-immunotherapy cohort. Our cohort validated the value of KMT2C mutations in predicting better clinical outcomes, including ORR (P < 0.0001) and OS (P = 0.010). Meanwhile, KMT2C mutation was associated with higher tumor mutation burden, MSI score, higher levels of immune-associated T cells, neutrophil, and M1-type macrophages. Our study suggested that KMT2C mutation might be a potential positive predictor for CRC immunotherapy.